2022
DOI: 10.3390/ijms232315390
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0011129 Encapsulated by the Small Extracellular Vesicles Derived from Human Stem Cells Ameliorate Skin Photoaging

Abstract: Photoaging is not only the main cause of skin aging caused by exogenous factors, it is also related to a variety of skin diseases and even malignant tumors. Excessive and repeated exposure to ultraviolet radiation, especially UVA induces oxidative stress, DNA damage, inflammation, and collagen and elastin degeneration, ultimately leads to skin photoaging, manifested by skin redness, coarse wrinkles, and pigmentation even skin cancer. There has been a large demand of effective prevention and medications but app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Exosomes stimulate collagen production in photoaged skin and reduce the appearance of pigmentation [4]. Moreover, photoaging is associated with a greater risk of malignant tumors like melanoma [109]. Thus, treatment of skin photoaging has important clinical significance and exosome-based therapy could be a helpful method not only in cosmetic application but also in skin cancer prevention.…”
Section: Clinical Applicability Of Exosomes In Photoaging: Current St...mentioning
confidence: 99%
“…Exosomes stimulate collagen production in photoaged skin and reduce the appearance of pigmentation [4]. Moreover, photoaging is associated with a greater risk of malignant tumors like melanoma [109]. Thus, treatment of skin photoaging has important clinical significance and exosome-based therapy could be a helpful method not only in cosmetic application but also in skin cancer prevention.…”
Section: Clinical Applicability Of Exosomes In Photoaging: Current St...mentioning
confidence: 99%
“…UV radiation can induce the mitochondria-dependent generation of ROS, which can inflict oxidative damage upon DNA bases [ 125 ]. ROS, including superoxide anions, hydroxyl radicals, and H 2 O 2 , serve as essential players in cell signaling and the maintenance of cellular homeostasis.…”
Section: Applications Of Msc-derived Evs Against Skin Agingmentioning
confidence: 99%
“…Zhang et al . [ 125 ] found that circ_0011129, a non-coding circular RNA, functions as a miR-6732-5p adsorption sponge, thereby impeding the degradation of type I collagen and the aggregation of elastin in a UVA-induced photoaging model of human dermal fibroblast cells. To improve the in vivo stability and delivery efficiency of circRNAs, the authors prepared extracellular vesicles loaded with circ_0011129 (3D-circc-sEV) by overexpressing circ_0011129 in ADSCs and culturing them in a 3D bioreactor.…”
Section: Administration Routes and Engineering Of Msc-evsmentioning
confidence: 99%
“…3 More advantageous in their biological function due to their small size, great stability, low cytotoxicity, immunogenicity, and target specificity (especially exosomes). 35 Limitations Products are highly heterogeneous due to the difficulty of purifying the specific therapeutic components. 54 Technical challenges in isolation and purification.…”
Section: Secretomes Evsmentioning
confidence: 99%
“…60 When observed through an electron microscope, exosomes have a typical "disk-like" structure and flat spherical shape. 35,36 EVs develop from larger intracellular vesicles known as multivesicular bodies (MVBs). MVBs are intraluminal vesicles (ILVs) formed by endosomal membrane internal budding.…”
Section: Secretomes Evsmentioning
confidence: 99%